PEMANFAATAN LIMBAH TANDAN KOSONG SAWIT (TKS) SEBAGAI MATERIAL ALTERNATIF DALAM PEMBUATAN BADAN WAHANA TERBANG TIPE FIXED WING ATHA MAPPER 2150 - Kaspul Anuar; Warman Fatra; Anita susilawati (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
To improve the application and use value of Palm Oil Empty Fruit Bunch (OPEFB) waste as a composite material, the research team conducted research related to the utilization OPEFB fiber as an alternative material to replace carbon fiber in the manufacture of fuselage of Unmaned Aerial Vehicle (UAV). The low price of OPEFB, low of specific density and it’s abundant availability are the basis of research to apply it’s fiber as material of UAV fuselage. This research begins with the processing of OPEFB into fiber through an alkali treatment process. Furthermore, the process of maleated natural rubber as a mixture of resin matrix. Afterward, the fuselage is molded use hybrid fiberglass-OPEFB fiber and resin epoxy that has been mixed with natural rubber. Fuselage of UAV is also molded with material of hybrid fiberglass-fibercarbon. Based on mass measurements, the fuselage of hybrid fiberglass-OPEFB fiber material and the fuselage of hybrid fiberglass-carbon fiber material have a mass of 510 grams and 540 grams respectively. For deflection measurement, fuselage of hybrid fiberglass-OPEFB fiber material has a maximum deflection as 2.01 mm, while the fuselage of hybrid fiberglass-fibercarbon material has a maximum deflection as 1.19 mm. In statis impact test, the two fuselage are able to withstand shock load.